Antioxidant Activities of Glycyrrhiza glabra L. and Momordica charantia L. Collected From Kahramanmaraş Charantia L. Collected From Kahramanmaraş Kahramanmaraş, Türkiye - Ayşegül Gölcü; Hatice Elmacioglu; Beril S. Kaya; Abdullah Al Faysal (Pharmata)
Objective: Türkiye is one of the countries that are rich in plant biodiversity. This geographical structure and climatic conditions of Kahramanmaraş allow various plant species to coexist. The usefulness of bioactive molecules as a source of novel antioxidant chemicals may be revealed by studies aimed at determining the antioxidant activity of plant species. The antioxidant capacity of the crude products from two Kahramanmaraş plants, licorice (Glycyrrhiza glabra) and bitter melon (Momordica charantia L.), was examined. Methods: This study systematically investigates, for the first time, various combinations of temperature, stirring rpm and time, and solvent to optimally extract the bioactive properties from these plants. Using ferric ion antioxidant potential (FRAP) reduction and DPPH (1,1-diphenyl-2-picrylhydrazyl free radical) scavenging tests, the antioxidant capabilities of plant extracts were investigated. Additionally, measurements were made of their total polyphenol levels (TPC), copper (II) ion reducing antioxidant capacity (CUPRAC), and iron (II) chelation activity (FIC). Results: The results of the FRAP assay and the DPPH assay showed a good connection, suggesting that the extracts included chemicals that could reduce ferric ions and scavenge free radicals. A strong association between TPC and other findings indicated that the extracts' polyphenols contributed to some of the antioxidant activity. Conclusion: The investigation indicates that consuming these plants would have a lot of advantageous effects due to the antioxidant properties they possess.